Uveitis or not? Diagnostic doubts in the pediatric age group - Rogulska, Katarzyna; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
Many localized and systemic diseases in children may occur with symptoms observed during uveitis, or symptoms that may imitate uveitis. These include neoplastic diseases, such as: leukemia, lymphomas, Langerhans cell histiocytosis, retinoblastoma, medulloepithelioma, uveal melanoma and non-cancerous illnesses: juvenile xanthogranuloma, retinal detachment, persistent hyperplastic primary vitreous, Coats’ disease and pigment dispersion syndrome. It is often difficult or even impossible to cooperate with young children during an ophthalmological examination, which makes the detection of subtle changes inside the eyeball even more challenging. The proper diagnosis may decide upon the right treatment at the early stage and thus improve the prognosis not only in terms of visual acuity, but also as far as the child’s life is concerned.